Estudio de farmacovigilancia para evaluar la seguridad y efectividad de losartán en hipertensos de 50 a 64 años. - Zapata Cáceres, Kelly Maribel (2017)
Hypertension is a chronic pathological process consisting of increased pressure outside the ranges considered normal (<130 / <85 mm / Hg), while values of (140/90 mm / Hg) are already considered As high and risky; This cardiovascular disease must be controlled periodically, because one of its characteristics is that it does not present clear symptoms and are not manifested for a long time. Therefore, through the exhaustive work carried out by the Pharmaceutical Biochemist during pharmacovigilance, which is a public health activity whose objective is the detection, evaluation, understanding and prevention of the adverse or secondary effects of medications, and any other related problems With the same is intended to reduce the morbidity and mortality rate of this disease in Ecuador and the world. The present work detailed the methodological framework based on observation, pharmacological follow-up, data collection in clinical records, conferences, and the application of surveys to hypertensive patients aged 50-64 years, corresponding to the study population, during the first Semester of the year 2017 in the general basic hospital Maria Lorena Serrano located in the corner El Guabo, province of El Oro. In this research 160 cases of patients with hypertension were analyzed where the following results can be denoted; About 83.10% of the population has knowledge of the disease whereas 16.90% do not, among the factors that produce this disease is the genetic or hereditary 66% have this history and 34% do not, so it is suspected that They acquired it by other factors, among the diseases that are related to hypertension is found first Diabetes mellitus with 50% unlike other diseases such as kidney failure with 24%, and obesity with 6%; In terms of treatment, patients stated that they had certain side effects, most of them stomach irritation and joint pain. Adverse reactions were observed in 9 of the 160 patients studied. The most common were arthralgias present in 5 of these patients, And among the less common are mixed nephropathy, myalgias and headaches. Finally, the effectiveness of the drug was evaluated in its two presentations Losartan 50 and 100 mg giving a total of 89% of patients satisfied with this treatment compared to 11% who did not feel any improvement due to the lifestyle they lead, The consumption of alcohol, foods rich in salt, lack of physical activity and by logic the sedentarismo, as well as not taking the correct dose nor in the schedule established by the doctor. The proposal of this research, which is to evaluate the safety and effectiveness of the Losartan drug, has manifested itself positively, obtaining excellent results and demonstrating the efficiency of our work, which was evidenced by the elaboration of a control plan in order to Improve the lifestyle of these patients, concluding that Losartan is safe, effective and of high quality.